(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2018)
Background: Antenatal corticosteroids have been shown to reduce complications that arise from preterm birth. Globally, the prevalence of preterm birth is 11.1%, with 60% of neonatal mortality in developing countries being due to preterm births. In Sub-Saharan Africa and Kenya, the preterm birth rate is 18% and 12% respectively. Currently, there is no consensus on the optimal dosing of antenatal corticosteroids. However, authors agree that they should be administered even when delivery is anticipated within 12 hours. Therefore, does incomplete dosing of dexamethasone confer any benefit to premature neonates? Objective: To compare the early neonatal outcomes among mothers who had preterm premature rupture of membranes (PPROM) and received two 12 mg doses of dexamethasone to those who received one 12-mg dose of dexamethasone between 28 to 34 weeks of gestation at KNH Methods: A retrospective cohort study involving neonates of mothers who had preterm premature rupture of membranes at 28 to 34 weeks gestation in KNH in the period between January 1, 2011, and December 31, 2015 and received either two 12 mg doses of dexamethasone (exposed group) or one 12-mg dose (unexposed group). The groups were compared for early neonatal outcomes. Sample size of 328 neonates was calculated, with 164 neonates in each arm. Results: There were no differences in the early neonatal outcomes (Apgar score <7 at 5 minutes, RDS, NEC, mortality and duration of hospital stay) apart from neonatal septicemia which was higher in the two 12- mg dexamethasone cohort (RR 0.78, 95%CI 0.62 to 0.99; p=0.039). Subgroup analysis by gestational ages showed increased neonatal mortality in the single 12-mg dose group (RR 2.09 95%CI 1.11-3.93; p=0.023). Conclusion: The incidence of early neonatal outcomes of mothers with preterm PROM at 28 to 24 weeks gestation at KNH in 2011 to 2015 were similar for mothers who received two doses of 12 mg dexamethasone and those who received single dose dexamethasone dose apart from early neonatal septicemia which was increased in the two 12 mg dexamethasone group.